Web based Me-centric Resource Management System for Pervasive Environment - 서대일; 안상철; 고희동 (Springer Verlag, 2013)
This paper presents a design and implementation of a web-based scalable me-centric resource management platform to support pervasive applications. The proposed system, LinkMe, builds me-centric overlay network, a private network of resources, for managing devices located in the user’s situated environment, as permitted resources. A resource may be atomic or a set of fine-grained resources. By this resource hierarchy, pervasive applications can choose a variety of resources combinations based tasks situated in the physical environment. Using web, resources are identified by URI and can be manipulated using HTTP verbs. Pervasive application can access resources using a set of RESTful APIs. To reduce technical barrier, developers can choose proper resources using URI and build a pervasive application easily based on web technologies such as HTML5, CSS and JavaScript.